[Real Effects of Foreign Surplus Disposal in Underdeveloped Economies]: Further Comment - Falcon, Walter P. (Quarterly Journal of Economics, 1963)
Journal Article Further Comment Get access Walter P. Falcon Walter P. Falcon Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 77, Issue 2, May 1963, Pages 323–326, https://doi.org/10.2307/1884407 Published: 01 May 1963